2019
DOI: 10.1111/aogs.13780
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mifepristone and misoprostol for medical treatment of missed miscarriage in clinical practice—A cohort study

Abstract: Introduction It has been estimated that one out of every four women experience first‐trimester miscarriage. Missed miscarriage is a common form of early miscarriage where the products of conception are not expelled from the uterus. It is diagnosed by ultrasound. The primary objective of this study was to evaluate the success rate of a combination treatment with mifepristone and misoprostol for missed miscarriage in clinical practice. The secondary objective was to identify significant factors influencing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
3
9
1
Order By: Relevance
“…Prior studies by Kim et al portrayed such association, which is contrary to that of Reeves et al and Ehrnstén et al, who stated that the possibility of a successful outcome decreases as gestational age and parity advance since the stretching of uterine muscles and loss of muscle integrity lead to poor response to medical termination. This relationship was most striking in ≥ para 5 patients; this may explain the apparent contradiction with the current study as the mean parity was 4 in our patients [8][9][10]. This study shows there is a strong relationship between predicting good responder and vaginal delivery.…”
Section: Discussioncontrasting
confidence: 92%
“…Prior studies by Kim et al portrayed such association, which is contrary to that of Reeves et al and Ehrnstén et al, who stated that the possibility of a successful outcome decreases as gestational age and parity advance since the stretching of uterine muscles and loss of muscle integrity lead to poor response to medical termination. This relationship was most striking in ≥ para 5 patients; this may explain the apparent contradiction with the current study as the mean parity was 4 in our patients [8][9][10]. This study shows there is a strong relationship between predicting good responder and vaginal delivery.…”
Section: Discussioncontrasting
confidence: 92%
“…Therefore, it is possible that some cases with documented histologically proven RPOC and early D&C might have resolved spontaneously if they had chosen a more expectative approach. The overall success rate in this study (83.1%—defined as no histologically confirmed RPOC in a D&C within three months) was comparable to success rates in other recent prospective studies (83–85%—defined as no surgical intervention to complete the miscarriage up to discharge) [ 9 , 16 ]. However, it is mentionable that the overall D&C-rate was 24.7%, which shows on the one hand the known difficulties in interpreting sonographic results after incomplete expulsion [ 17 ], but on the other hand maybe as well that persistent decidual tissue can cause bleeding disorders and pain [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it was suggested that expectant management may be useful and appropriate for first-trimester miscarriages after RT [12]. Although the use of mifepristone and/or misoprostol for the treatment of an early miscarriage has been reported to have a high success rate in patients without a history of RT [13,14], there are no data evaluating the efficacy of any medication to treat miscarriage in patients after RT.…”
Section: Counseling About Perinatal Management Before Pregnancymentioning
confidence: 99%